Emotional intelligence: a comparison between patients after first episode mania and those suffering from chronic bipolar disorder type I - Cristina Varo; Silvia Amoretti; Giulio Sparacino; Esther Jiménez; Brisa Solé; Caterina del Mar Bonnin; Laura Montejo; Maria Serra; Carla Torrent; Estela Salagre; Antoni Benabarre; Pilar Salgado-Pineda; et al. (My University, 2022)
Abstract Background Deficits in emotional intelligence (EI) were detected in patients with bipolar disorder (BD), but little is known about whether these deficits are already present in patients after presenting a first episode mania (FEM). We sought (i) to compare EI in patients after a FEM, chronic BD and healthy controls (HC); (ii) to examine the effect exerted on EI by socio-demographic, clinical and neurocognitive variables in FEM patients. Methods The Emotional Intelligence Quotient (EIQ) was calculated with the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT). Performance on MSCEIT was compared among the three groups using generalized linear models. In patients after a FEM, the influence of socio-demographic, clinical and neurocognitive variables on the EIQ was examined using a linear regression model. Results In total, 184 subjects were included (FEM n = 48, euthymic chronic BD type I n = 75, HC n = 61). BD patients performed significantly worse than HC on the EIQ [mean difference (MD) = 10.09, standard error (s.e.) = 3.14, p = 0.004] and on the understanding emotions branch (MD = 7.46, s.e. = 2.53, p = 0.010). FEM patients did not differ from HC and BD on other measures of MSCEIT. In patients after a FEM, EIQ was positively associated with female sex (β = −0.293, p = 0.034) and verbal memory performance (β = 0.374, p = 0.008). FEM patients performed worse than HC but better than BD on few neurocognitive domains. Conclusions Patients after a FEM showed preserved EI, while patients in later stages of BD presented lower EIQ, suggesting that impairments in EI might result from the burden of disease and neurocognitive decline, associated with the chronicity of the illness.
Keywords: bipolar disorder; emotional intelligence; first episode mania; msceit; verbal memory; bipolar disorder; cognition; emotional intelligence; emotions; female; humans; mania; bipolar disorder; cognition; emotion; emotional intelligence; female; human; mania; psychology